The influence of copper addition on the corrosion behaviour of low nickel austenitic stainless steels - Vismer, Suzanne Lisa (Centre for Materials Engineering, 2024)
[page ii missing] The influence of copper and nitrogen as partial substitutes for nickel on the corrosion performance of three metastable austenitic stainless steels, in various microstructural conditions, has been investigated. These alloys (based on AISI 301), which are to be used essentially in forming applications, were developed to counteract the increasing cost of nickel. Copper and nitrogen are both cheap and readily available alternative alloying additions. While nitrogen has been found to enhance the mechanical properties of austenitic stainless steels, copper is said to prevent delayed cracking after deep drawing. The experimental alloys contain nominal amounts of 17Cr-5.4Ni-0.25N (wt%) with copper additions ranging from 0 to 3.3 wt%. Characterisation of the corrosion performance of these alloys involved testing in the solution treated, solution treated and aged, solution treated and deformed and the solution treated, deformed and aged conditions. These tests included potentiodynamic scans, polarisation resistance measurements and Tafel plots conducted in 5 volume % de-aerated sulphuric acid solution at 30°C as well as pitting tests in NaCl solutions. The results showed that all three alloys displayed the lowest corrosion rates in the solution treated condition. The corrosion rates of the alloys in the solution treated and aged condition did not vary significantly with ageing time. Microscopy, however, revealed an increase in intergranular corrosion attack with ageing time. Thus, potentiodynamic tests did not seem a suitable method for quantifying. the influence of copper on the sensitisation of these alloys. During deformation at room temperature, copper was found to stabilise the austenite resulting in more martensite being formed in the copper-free alloy. This martensite is expected to decrease corrosion resistance which could account for the copper-free alloy's relatively high corrosion rates in the solution treated and deformed condition. Deformation carried out at different temperatures, but to equivalent strains, allowed equal amounts of martensite to be achieved amongst the alloys. In this way, corrosion tests revealed that copper was found to reduce the dissolution rate of martensite. Following deformation (at controlled temperatures) and ageing, copper did not appear to influence the precipitation kinetics leading to sensitisation of the martensite. For all microstructural conditions, the copper-containing alloys consistently exhibited the highest corrosion resistance. Comparisons with the standard AISI 301 and 304L alloys showed that the copper-containing novel alloys showed superior corrosion resistance. The corrosion characterisation conducted in this thesis of these novel copper-containing alloys, proves that these alloys look promising as substitutes for the conventional alloys presently used in forming applications.